2016
DOI: 10.1371/journal.pone.0165077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Role of Hexamer AGUAAA and Poly(A) Tail in Coronavirus Polyadenylation

Abstract: Similar to eukaryotic mRNA, the positive-strand coronavirus genome of ~30 kilobases is 5’-capped and 3’-polyadenylated. It has been demonstrated that the length of the coronaviral poly(A) tail is not static but regulated during infection; however, little is known regarding the factors involved in coronaviral polyadenylation and its regulation. Here, we show that during infection, the level of coronavirus poly(A) tail lengthening depends on the initial length upon infection and that the minimum length to initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…This is in accordance with the results obtained by (Hassan et al, 2020). (Peng et al, 2016), of which only four sequences Wuhan Reference, Hyderabad (Telangana), South 24 Parganas, and Howrah (West Bengal) (viz., NC_045512, EPI_ISL_431102, 437537, 437537) had a poly-A tail after 57 bases. The remaining sequences were terminated between 53-58 bases downstream, without a poly-A tail.…”
Section: Shannon Entropysupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the results obtained by (Hassan et al, 2020). (Peng et al, 2016), of which only four sequences Wuhan Reference, Hyderabad (Telangana), South 24 Parganas, and Howrah (West Bengal) (viz., NC_045512, EPI_ISL_431102, 437537, 437537) had a poly-A tail after 57 bases. The remaining sequences were terminated between 53-58 bases downstream, without a poly-A tail.…”
Section: Shannon Entropysupporting
confidence: 92%
“…The first available SARS-CoV-2 isolate from Kerala (EPI_ISL_413522) is devoid of polymight signify a different origin of the Indian isolate when compared to the Chinese isolate, or it may denote an indel (Chatterjee, 2020) as it is well known that the poly-A tail plays a significant role during infection. Truncation of the poly-A tail in Kerala isolate is probably due to sequencing errors or may be due to tail length regulation in coronavirus as the length is not static (Peng et al, 2016). However, it cannot signify a Chatterjee (2020).…”
Section: Shannon Entropymentioning
confidence: 99%
“…Studies from influenza virus revealed that a short polyU sequence within a unique RNA stem−loop mediates a stuttering mechanism used to polyadenylate the positive-sense RNA (45). In contrast, Peng et al (46) implicate that CoVs utilize a noncanonical cytoplasmic polyadenylation site to synthesize the positive-sense polyA tail. They identified a conserved viral sequence on the positive-sense RNA that could be bound by host proteins, including cytoplasmic polyadenylation element binding protein 1 (CPEB1) (47), a protein that mediates polyadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…Various deletions and insertions in the 3= UTR as well as complete deletion of the poly(A) tail may not kill alphaviruses (457)(458)(459), flaviviruses (460)(461)(462), coronaviruses (463)(464)(465), and various plant viruses (466)(467)(468)(469). The repair of the damaged genomes may again involve different mechanisms, including RNA recombination, the use of the viral RdRP-or host-dependent polyadenylation activities, and perhaps some others.…”
Section: Some Additional Lessons From Other Rna Viruses Positive-stramentioning
confidence: 99%